Assessment of drug therapy problems among hypertensive patients at integral institute of medical science and research - Kapoor, Ayushi; Asiya Aluminium, Mustapha; Manger, Sameer; Usman, Isah; Sada, Mudassir; Akhter, M. Sohel; Parmar, Vishal (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Drug therapy problems (DTP) encompass a range of categories. These include untreated indications, overdose, wrong choice of drugs, adverse drug reaction, drug-drug interaction, need for monitoring, and non-adherence etc. by recognizing and addressing these various drug related problems, healthcare professionals can optimize treatment outcomes and ensure patient safety. Aim was to assess DTP among hypertensive patients at IIMS&R hospital Methods: Over a period of six months, a prospective observational study involving 107 subjects was conducted at IIMS&R hospital, Lucknow department of general medicine. Information about patient demographics, co-morbidities, and drug therapy problems in treatment of hypertension were collected and analyzed, and the results were expressed as percentages. Results: In the study, 12 different types of antihypertensive medications were prescribed in a total of 225 drugs. Telmisartan, amlodipine, torsemide, and furosemide emerged as the most commonly prescribed medications. Telmisartan was frequently prescribed orally, while furosemide was primarily administered intravenously. Drug therapy problems such as untreated indication, lack of patient compliance, adverse drug reactions (ADRs) and potential interactions were found Conclusions: The study highlighted the importance of monitoring and addressing potential drug interactions, medication adherence were common drug therapy problems. This underscores the immediate need for health education and sensitization initiatives targeted at individuals with hypertension, aiming to improve the overall quality of life for these patients.